New inflammatory markers in pre-eclampsia: echocardiographic epicardial fat thickness and neutrophil to lymphocyte ratio. (November 2014) - Oylumlu, Mustafa; Ozler, Ali; Yildiz, Abdulkadir; Oylumlu, Muhammed; Acet, Halit; Polat, Nihat; Soydinc, Hatice Ender; Yuksel, Murat; Ertas, Faruk
Abstract Background: Increased epicardial fat thickness (EFT) has been proposed as a new cardiometabolic risk factor. The neutrophil/lymphocyte ratio (NLR) has predictive and prognostic value in several cardiovascular diseases. The aim of this study was to explore the association between EFT and NLR in patients with pre-eclampsia. Methods: Hundred and eight pregnant patients with a mean age of 30.6 ± 6.3 years were included in the study. Patients were divided into two groups based on the presence of pre-eclampsia. All participants underwent transthoracic echocardiography imaging, and complete blood counts were measured by an automated hematology analyzer. Statistical analysis was performed using the Chi-square, Mann–Whitney U, correlation and logistic regression tests, and receiver operating characteristic (ROC) analysis. Result: The mean EFT value of the pre-eclampsia group was significantly higher than the control group (6.9 ± 0.6 versus 5.6 ± 0.6; p < 0.001), and the NLR value of the pre-eclampsia group was also significantly higher than the control group (7.3 ± 3.5 versus 3.1 ± 1.1; p < 0.001). Multivariate analysis showed that increased levels of NLR and echocardiographic EFT are independent predictors of pre-eclampsia. In the receiver operating characteristic analysis, a level of EFT ≥ 6.2 mm and NLR ≥ 4.1 predicted the presence of pre-eclampsia with 77.8% sensitivity, 79.6% specificity and 83.3% sensitivity, 81.5% specificity, respectively. Conclusion: Unlike many other inflammatory markers and bioassays, NLR and echocardiographic EFT are inexpensive and readily available biomarkers that may be useful for risk stratification in patients with pre-eclampsia.